2020
DOI: 10.1111/nhs.12769
|View full text |Cite
|
Sign up to set email alerts
|

Negative workplace behavior and coping strategies among nurses: A cross‐sectional study

Abstract: Negative workplace behavior affecting nurses is an internationally recognized problem. This study examines the types and extent of negative workplace behavior experienced by nurses in non-metropolitan, regional acute care settings and their ways of coping when subject to that behavior. A cross-sectional study was conducted involving 74 nurse participants in four regional hospitals in Australia. The structured questionnaire consisted of four parts: demographic questions, the Negative Acts Questionnaire-Revised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 39 publications
1
32
0
5
Order By: Relevance
“…In doing so, we answer the calls for further research to detect potential mediators of the outcomes of workplace incivility (Yao et al, 2021). Third, we analyse whether social support seeking, which is one of the coping strategies most commonly reported by healthcare providers to deal with negative workplace behaviours (Hawkins et al, 2021), can mitigate the detrimental effects of victim incivility and work-tofamily conflict on emergency workers' well-being. While the protective effect of social support against burnout has been well-documented (Velando-Soriano et al, 2020), mixed results have been revealed with reference to social support seeking.…”
Section: Victim Incivility and Emergency Workers' Burnoutmentioning
confidence: 97%
See 3 more Smart Citations
“…In doing so, we answer the calls for further research to detect potential mediators of the outcomes of workplace incivility (Yao et al, 2021). Third, we analyse whether social support seeking, which is one of the coping strategies most commonly reported by healthcare providers to deal with negative workplace behaviours (Hawkins et al, 2021), can mitigate the detrimental effects of victim incivility and work-tofamily conflict on emergency workers' well-being. While the protective effect of social support against burnout has been well-documented (Velando-Soriano et al, 2020), mixed results have been revealed with reference to social support seeking.…”
Section: Victim Incivility and Emergency Workers' Burnoutmentioning
confidence: 97%
“…Social support seeking, which combines both instrumental and emotional social support, is one of the ways of coping with negative workplace behaviour, including workplace incivility, most commonly reported by healthcare workers (Hawkins et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative workplace behavior and coping strategies among nurses: a crosssectional study* (19) Hawkins (21) Molero J., et al 2021 España Analizar la relación entre la inteligencia emocional y el mobbing percibido por las enfermeras y establecer los papeles mediadores de otras variables como el apoyo social y la sensibilidad a la ansiedad.…”
Section: 10unclassified